1981
DOI: 10.1159/000232766
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E-Containing Cells in Mouse Lung Following Allergen Inhalation and Ozone Exposure

Abstract: Cells containing immunoglobulin E (IgE) were enumerated and their location in mouse lungs was determined by direct immunofluorescence. Lungs were studied from mice that had been immunized with aerosolized ovalbumin as well as from normal mice and from mice that were exposed to ozone (0.5 or 0.8 ppm) prior to receiving aerosolized antigen. In addition, some mice were immunized intraperitoneally with ovalbumin precipitated in alum. IgE-containing cells were primarily airway-related in normal mice and in mice imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…However, little is known concerning the regulation of IgE antibody production by aerosolized antigens in animals, since the administration of aerosolized anti gens hardly produces IgE antibody [2] and the meth ods of aerosol administration have not been suffi ciently studied. In this study, the effect of administra tion of aerosolized antigen on the induction of IgE antibody production in mice is reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known concerning the regulation of IgE antibody production by aerosolized antigens in animals, since the administration of aerosolized anti gens hardly produces IgE antibody [2] and the meth ods of aerosol administration have not been suffi ciently studied. In this study, the effect of administra tion of aerosolized antigen on the induction of IgE antibody production in mice is reported.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental models, adminis tration of antigens into the lungs results in the forma tion of antibodies, particularly of the IgA, IgM and IgG isotypes [6], Antibody responses of the IgE iso type have also been reported by some authors [1,2,17,18,24,26], but not by others [ 16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal studies revealed that S 0 2 increases the sensitivity of animals to develop anaphylactic reaction in response to the sensitizing agent (ovalbumin) presumably by increasing the respiratory epithelial permeability [8]. Ozone induces the high number o f IgE-containing cells in the lungs [9]. Partic ulates from diesel exhausts enhance allergen-specific IgE responses [10].…”
mentioning
confidence: 99%